Barriers and facilitators of intention to organ donation among general people in state of Puducherry: a cross sectional study - Arunachalam, D.; Subash Chandrabose, G. (International Journal Of Community Medicine And Public Health, 2017)
Background: Organ transplantation is taken into account one among the best advances of contemporary science that has given several patients a revived lease of life. The target of study resolve the barrier and supporter of organ donation among general public, and to spot the factors that influence organ donation assent and rejection in state of Puducherry, India. Methods: A cross-sectional study had below soft on a sample of a hundred and fifty subjects handily. The eligible subjects were administered a structured inquiries to assume barriers and facilitators of organ donation. The collected information’s were statistically analyzed. Results: Of the one hundred fifty subjects, the age groups were 58% 20-30 years, 26% 31-40 years, 12% 41 to 50 years and 4% 51-60 years. Male constituted 33.3% and females were 66.7% of the subjects. The mean data score of the themes were 4.74±1.45 (1-8). 80.6% according the intention to gift organ and 19.3% weren't willing to gift organ. The foremost necessary barriers were opposition from family (82.8%) and concern (72.4%). The foremost necessary facilitators were organ donation would save someone’s life (95.9%) and it improve the sense of human (95%). Education, occupation, married and financial gain square measure related to intention to gift organ. Conclusions: From the offered scientific proof it's conducted that information of organ donation stay still poor and therefore the indentified barriers and facilitators ought to be taken within the account whereas motivates the overall peoples to present organ to future.